After Urban Regeneration : Communities, Policy and Place - Matthews, Peter (Of University of Stirling); O'Brien, Dave (Book collections on Project MUSE., 2016)
Focusing on the history and theory of community in urban policy, and including a unique set of case studies that draw on artistic and cultural community work, this book engages with debates on how urban policy has changed and continues to change following the financial crash of 2008.